Highly sensitive in-line microfluidic sensor based on microfiber-assisted Mach–Zehnder interferometer for glucose sensing. (13th October 2017) - Xie, Nanjie; Zhang, Hao; Liu, Bo; Wu, Jixuan; Song, Binbin; Han, Tingting
Abstract: A highly sensitive microfluidic sensor based on a microfiber-assisted Mach–Zehnder interferometer (MAMZI) is proposed and experimentally demonstrated for the detection of low-concentration glucose solution. A segment of microfiber tapered from standard single-mode fiber (SMF) is spliced between two SMFs with pre-designed lateral offset to constitute the miniaturized MAMZI probe. The transmission spectral response to environmental refractive index variation has been experimentally investigated for glucose concentration ranges of 300 mg dL −1 to 3000 mg dL −1 and 0 to 270 mg dL −1 and the glucose concentration detection limit is 3 mg dL −1, and the experimentally observed transmission spectral responses are in accordance with our theoretical simulation results. Owing to its high sensitivity, non-enzymatic operation method, ease of fabrication and compact size, our proposed MAMZI for glucose sensing is anticipated to be employed in biomedical applications.